LA DECLARACIÓN MAGISTRAL DE DIEGO LÓPEZ A LAS SÁTIRAS DE PERSIO: PRECISIONES LINGÜÍSTICAS. (I) - Fortuny Previ, Filomena (Myrtia, 1999)
Diego López, pupil of Sánchez de las Brozas and Nebrija, commented and analyzed the Satires of Persius in his work Declaración Magistral de Diego López a las Sátiras de Persio. The purpose of this humanist was to facilitate the understanding of the Latin authors to the scholars and therefore he used spanish language. The explanations of the Satires given by López include a lot of fields: stylistic, story of customs, mythological, historial, etc. The present work focuses particularly on his linguistic glosses, which denote López's wide knowledges of Latin language